Production Techniques of Nauplii Whiteleg Shrimp (Litopenaeus vannamei) The Results of Mass Spawning - Akbarurrasyid, Muhammad; Sofian, Achmad; Huda, Wildan Khorul; Sudinno, Dinno; Prajayati, Vini Taru Febriani; Sembiring, Kennedi (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2025)
Litopenaeus vannamei farming intensively cannot be separated from various problems. One of the problems faced by farmers is the availability of seeds in terms of quantity and quality. Therefore, this study aims to determine the production techniques of L. vannamei shrimp nauplii produced from the mass spawning process to support the increase in the number of L. vannamei shrimp production. Mass spawning has an impact on the number of nauplii produced and the effectiveness of broodstock maintenance. This study was carried out in Banten, Indonesia. This study was conducted by surveying and observing the stages of broodstock management, spawning, nauplii harvesting, and the production of nauplii. The results of the study showed that several aspects must be considered: (1) broodstock management that includes feeding and monitoring water quality, (2) mass spawning, and (3) harvesting and production of nauplii. During the rearing period, feed, such as pellets, marine worms, and squid, was administered to accelerate the gonad maturation process, and water quality was controlled. The results of mass spawning were obtained Maturation Rate ranges 12.66 - 21.66%, Matting Rate (MR) ranges 40 - 85%, Fecundity ranges 231,951 – 486,250 eggs/shrimp, Fertilization Rate (FR) ranges 60.45 – 72.37%, and Hatching Rate (HR) ranges 71.66 – 87.24%. Total nauplii production was 4.996.398 shrimp for 28 days. Total production was slightly lower than previously reported, which was caused by an inaccurate matting process.